Cattle Fattening Program: The Effectiveness of Zakat Community Development - Bambang Iswanto; Iklimah Dalhudah; Mursyid Mursyid; Idhafiyyah Anwar (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Despite many studies on productive Zakat, the focus on the effectiveness of mustahiq empowerment programs has been limited. This study looks at how effective the Zakat community development-based cattle fattening program is towards the empowerment of Zakat recipients. The study measures four indicators of program effectiveness: program target accuracy, program socialization, program objectives, and program monitoring. Data collection techniques include interviews, observation, and documentation. The study found that the program was good at targeting the right people, but it wasn't socialized enough. The program also fell short of its objectives because the recipients weren't making enough money to become donors themselves yet. However, the program was well-monitored, with regular check-ins to make sure it was on track. The study suggests that clearer standards are needed to increase the benefits received by Zakat recipients This study has practical implications for productive Zakat distribution policies, as clear benchmarks are required for implementing programs that increase Zakat recipients' benefits.